2016
DOI: 10.1186/s13018-016-0448-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the independent risk factors of neurologic deficit after thoracolumbar burst fracture

Abstract: BackgroundThe objective of this study is to identify the independent risk factors of neurologic deficit after thoracolumbar burst fracture. Traumatic fractures of the thoracolumbar spine are the most common type of spinal column fractures. Many studies have attempted to determine whether neurologic deficit in such fractures is related to spinal canal stenosis or other parameters observed on axial computed tomography. However, this relationship remains controversial.MethodsA review of the clinical data and axia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
11
0
5
Order By: Relevance
“…The thoracolumbar burst fracture is characterized by a falling height on the anterior margin of the vertebral body and damage to the posterior margin of the vertebral body. Upon encroachment of the posterior vertebral wall and posterior ligamentous complex, the posteriorly displaced fracture fragment encroaches into the spinal canal [ 18 , 19 ] with a high risk of neurological impairment [ 20 ]. Mohamed M. Aly et al [ 21 ] showed that the absence of horizontal laminar fracture, spinous process fracture, interspinous widening > 4 mm, and facet joint malignment has a high negative predictive value of PLC injury.…”
Section: Discussionmentioning
confidence: 99%
“…The thoracolumbar burst fracture is characterized by a falling height on the anterior margin of the vertebral body and damage to the posterior margin of the vertebral body. Upon encroachment of the posterior vertebral wall and posterior ligamentous complex, the posteriorly displaced fracture fragment encroaches into the spinal canal [ 18 , 19 ] with a high risk of neurological impairment [ 20 ]. Mohamed M. Aly et al [ 21 ] showed that the absence of horizontal laminar fracture, spinous process fracture, interspinous widening > 4 mm, and facet joint malignment has a high negative predictive value of PLC injury.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding neurological outcomes, our study found no significant differences among both approaches. Despite the fact that the surgical procedure aims to improve the patient's neurological status and avoid deterioration, to ensure an increase in the quality of life, it is noteworthy that the initial lesion itself is the main cause of decreased quality of life after BFs 9 and that certain computed tomography parameters (compression ratio of median sagittal diameter, anterior vertebral compression ratio, among others) observed before surgery have a strong association with the neurological deficit 32 .…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] is negative association has been explained by different theories including the different reserve capacity in the lumbar versus cervical/thoracic spine, the presence of the cauda equina nerve roots in the lumbar spine versus cervical/thoracic cord, and the energy/force resulting in different levels of spinal fractures. [3,[11][12][13][14] No correlation between the extent of spinal canal stenosis and the degree of the neurological deficit [4] (Contd...) Compression ratio of median sagittal diameter as risk factor of neurologic deficit after thoracolumbar burst fracture [12] C: Cervical, L: Lumbar, T: oracic, TL: oracolumbar, MR: Magnetic resonance, PR: Plain radiography, CT: Computed tomography…”
Section: Discussionmentioning
confidence: 99%